Knowledge of Maternal Mortality and Its Determinants Among Pregnant Women at Tamale Teaching Hospital in Northern Ghana: A Descriptive Cross-Sectional Study - Yakubu, Hajara; Ibrahim, Mudasir Mohammed; Dogbe, Patience; Issah, Nafisatu; Abosi, Kate; Osman, Adisah; Abangbila, Francisca; Abdulai, Abdul-Malik (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Maternal mortality remains a significant public health challenge in Ghana. Understanding the level of knowledge among pregnant women regarding maternal mortality is crucial for designing effective interventions. Purpose: To evaluate the knowledge of maternal mortality and its determinants among pregnant women at Tamale Teaching Hospital in the Northern Region of Ghana. Methods: An institution-based quantitative cross-sectional study was conducted at Tamale Teaching Hospital in the Northern Region of Ghana. A systematic random sampling technique was used to select 240 pregnant women attending ANC services at the facility. The data were analyzed using John's Macintosh Project (JMP) Statistical Software version 17.1. Results: The response rate in this study was 97.5%. The majority of pregnant women (52.6%) had good knowledge of maternal mortality, while 47.4% had poor knowledge. Significant determinants of knowledge of maternal mortality were educational level (OR=3.69, p=0.002), occupational status (OR=4.00, p=0.001), monthly income (OR=3.67, p=0.001), age at first pregnancy (OR=2.84, p=0.021), number of weeks in the current pregnancy (OR=0.41, p=0.041), previous history of intrauterine fetal distress (IUFD) (OR=5.01, p=0.021), presence of chronic illness (OR=7.93, p=0.001), and obstetric labor complications readiness (OR=8.93, p<0.001). Conclusion: Although the majority of pregnant women had good knowledge of maternal mortality, special attention should be given to women in the second trimester and those with previous histories of IUFD or chronic illnesses to address gaps in knowledge and ultimately reduce maternal mortality rates.